Comparative Analysis of Student-Centered Teaching Mode In Selected Colleges and Universities In China - XIE, CHUN; Ramirez, Mariano (Pacific International Journal, 2025)
At present, there are significant differences in the implementation and practice of student-centered teaching models among different universities in China, resulting in different teaching outcomes. This provides certain innovative space for the development of this research activity. This study mainly adopts a combination of quantitative and qualitative research methods to compare the practical effects of the student-centered teaching model in five selected universities. It is found that all five universities have commendable aspects in implementing the student-centered teaching model, and there are also many areas that can be improved and perfected. Researchers not only raised common issues and challenges, but also proposed the best practice model and provided suggestions.